Stenotrophomonas maltophilia: Significant contemporary hospital pathogen - review - Nyc, O; Matejková, J (Folia microbiologica, 2010)
Stenotrophomonas maltophilia (Sm) plays an important role as an opportunistic pathogen in immunocompromised individuals. The growing detection rates of this bacterium in hospitalized patients are associated with the invasiveness of therapeutic and diagnostic procedures and the selection pressure of antibiotic therapy. A broad range of infections that can be caused by Sm is frequently bound to biofilm. The high level of intrinsic resistance to many unrelated antibiotics and increasing acquired resistance to the drug of choice, trimethoprim-sulfamethoxazole pose a threat for the near future when our treatment options may become depleted. Prevention of colonization and infection consists in consequent implementation of the rules governing nosocomial infection control, rational use of antibiotics including the optimization of selection and testing of antimicrobial agents suitable for the treatment of stenotrophomonad infections.
Keywords: Gram-Negative Bacterial Infections; Humans; mnohočetná bakteriální léková rezistence; lidé; antibakteriální látky; kontrola infekce; Drug Resistance, Multiple, Bacterial; infekce spojené se zdravotní péčí; Stenotrophomonas maltophilia; Hospitals; Anti-Bacterial Agents; biofilmy; nemocnice; imunokompromitovaný pacient; gramnegativní bakteriální infekce; Infection Control; Immunocompromised Host; Biofilms; Cross Infection